Eye-Tracking Evidence of a Maintenance Bias in Social Anxiety. Issue 1 (22nd June 2017) - Fernandes, Catarina; Silva, Susana; Pires, Joana; Reis, Alexandra; Ros, Antónia Jimenez; Janeiro, Luís; Faísca, Luís; Martins, Ana Teresa
Abstract : Background: The mechanisms and triggers of the attentional bias in social anxiety are not yet fully determined, and the modulating role of personality traits is being increasingly acknowledged.Aims: Our main purpose was to test whether social anxiety is associated with mechanisms of hypervigilance, avoidance (static biases), vigilance-avoidance or the maintenance of attention (dynamic biases). Our secondary goal was to explore the role of personality structure in shaping the attention bias.Method: Participants with high vs low social anxiety and different personality structures viewed pairs of faces (free-viewing eye-tracking task) representing different emotions (anger, happiness and neutrality). Their eye movements were registered and analysed for both whole-trial (static) and time-dependent (dynamic) measures.Results: Comparisons between participants with high and low social anxiety levels did not yield evidence of differences in eye-tracking measures for the whole trial (latency of first fixation, first fixation direction, total dwell time), but the two groups differed in the time course of overt attention during the trial (dwell time across three successive time segments): participants with high social anxiety were slower in disengaging their attention from happy faces. Similar results were obtained using a full-sample, regression-based analysis.Conclusion: Our results speak in favour of a maintenance bias in social anxiety. Preliminary results indicated that personality structure may not affect the maintenance (dynamic) bias of socially anxious individuals, although depressive personality structures may favour manifestations of a (static) hypervigilance bias.